Navigating employment transformations: Insights into changes within service organizations - Nešić Tomašević, Ana; Grubić-Nešić, Leposava; Perić, Aleksandra (Hotel and Tourism Management, 2024)
Purpose – In today’s dynamic business landscape, service organizations are compelled to navigate constant transformations to adapt to market needs, anticipate shifts, and innovate to meet evolving customer demands. This study delves into the relationship between employees in service organizations and changes, aiming to ascertain organizational readiness for change, focusing on dimensions such as commitment to change implementation and the efficiency of implemented changes. Methodology – Employing the standardized Organizational Readiness for Implementing Change (ORIC) questionnaire, the research surveyed 319 employees in service organizations. Findings – Results highlight challenges in the subjective perception of potential organizational changes, affirming individual differences in attitudes toward change and a notably modest and inconsistent approach in fostering a positive attitude toward change. Variances in attitudes toward change are recognized not only in general demographic characteristics but also in organizational traits. Significantly, organizations often delegate the responsibility for managing change attitudes to individuals, consequently slowing down the change processes. Implications – This research endeavors to offer practical suggestions to organizations, directing them on algorithmic initiatives aimed at fostering favorable employee attitudes towards change.